Multifunctional Properties of Glycoside Hydrolase Family 43 from Paenibacillus curdlanolyticus Strain B-6 Including Exo-_-xylosidase, Endo-xylanase, and _-L-Arabinofuranosidase Activities - Kanok Wongratpanya; Siriluck Imjongjairak; Rattiya Waeonukul; Somphit Sornyotha; Paripok Phitsuwan; Patthra Pason; Thidarat Nimchua; Chakrit Tachaapaikoon; Khanok Ratanakhanokchai (My University, 2015)
The glycoside hydrolase family 43 from Paenibacillus curdlanolyticus strain B-6 (GH43B6) exhibited multifunctional properties, including exo-βxylosidase, endo-xylanase, and α-L-arabinofuranosidase enzymatic activities.GH43B6 released xylose as a hydrolysis product from the successive reduction of xylooligosaccharides as a result of exo-βxylosidase activity.Moreover, GH43B6 also predominantly released xylose from low-substituted xylan derived from birchwood.However, when the highly substituted rye flour arabinoxylan was used as a substrate, exo-β-xylosidase activity changed to endo-xylanase activity, indicating that the enzymatic property of GH43B6 is influenced by the substituted side groups of xylan.For α-L-arabinofuranosidase, arabinose was released from short-chain substrates including p-nitrophenyl-α-Larabinofuranoside and α-L-Araf-(1→2)-[α-L-Araf-(1→3)]-β-D-Xylp.This study reports the novel trifunctional properties of GH43B6 containing exoand endo-activity together with xylanolytic debranching enzymatic activity, which increases its potential for application in lignocellulosebased biorefineries.
Keywords: Arabinoxylan; Arabinose; Biofuel production and bioconversion